PEMBUATAN MULTIPLE CROWN PADA PEMAKAI PROTESA DEFINITIF KASUS MAKSILOFASIAL (LAPORAN KASUS) - Xeriny Lilian T. Hasan; Roselani W. Odang (Faculty of Dentistry, Universitas Indonesia, 2015)
Prosthodontics management of post hemimaxillectomy patient were different company to the principle parameters conventional. Treatment planning and design of definitive prostheses of the maxillofacial case need a careful examination so that it can anticipate and accomodate the prosthese movement during function so that it wouldn't give pathological stress on the teeth. The restoration on every maxillary defect will increase significantly if the teeth were present. The maintenance of the residual teeth will give better support to increase retention and stabilization of the prostheses so that the patient will geel comfortable, has an esthetical and psycholgical effect. This paper describes a case report where splinting of three anterior teeth adjacent to the defect with a multiple crown restoration, to protect these abutment teeth.